x+x+x+12+5*x=10*x-2

Simple and best practice solution for x+x+x+12+5*x=10*x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+x+x+12+5*x=10*x-2 equation:


Simplifying
x + x + x + 12 + 5x = 10x + -2

Reorder the terms:
12 + x + x + x + 5x = 10x + -2

Combine like terms: x + x = 2x
12 + 2x + x + 5x = 10x + -2

Combine like terms: 2x + x = 3x
12 + 3x + 5x = 10x + -2

Combine like terms: 3x + 5x = 8x
12 + 8x = 10x + -2

Reorder the terms:
12 + 8x = -2 + 10x

Solving
12 + 8x = -2 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
12 + 8x + -10x = -2 + 10x + -10x

Combine like terms: 8x + -10x = -2x
12 + -2x = -2 + 10x + -10x

Combine like terms: 10x + -10x = 0
12 + -2x = -2 + 0
12 + -2x = -2

Add '-12' to each side of the equation.
12 + -12 + -2x = -2 + -12

Combine like terms: 12 + -12 = 0
0 + -2x = -2 + -12
-2x = -2 + -12

Combine like terms: -2 + -12 = -14
-2x = -14

Divide each side by '-2'.
x = 7

Simplifying
x = 7

See similar equations:

| (3x^5/85^4)^-3 | | 9.5/1.25 | | 126-3(6x-6)= | | 4c+6=5c-9 | | 4x^2-76=3x | | 2x2y0(5xy2)2/5(-2xy2) | | 4x^2-7=-27x | | 5f+3= | | 5p=p-6 | | y=177-8x | | 4(4y+9)=50 | | 3a+10=a+38 | | 24x^2+22x+3=0 | | 4(x-1)-3=13 | | 8-18x=2-x | | 2-3(-9)=-7 | | 19.45=-8.6r+-12.8 | | 4t-8+14t=3-4t-11 | | 3v+19=5v-17 | | 2-3(5)=-7 | | 12s+20=17s | | 19a-8=15a | | 4/5-(-16/5) | | -5(8a-6)=-34-8 | | 2z+20=3z-9 | | 3p+13=p+15 | | p=5.65-.05(78.4) | | 328=8(6+5a) | | 5w-14=4w+4 | | X=5y*7 | | 3(x-1)=5x+4 | | 2x-k=-1 |

Equations solver categories